2007
DOI: 10.1002/14651858.cd004651.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Oral water soluble contrast for the management of adhesive small bowel obstruction

Abstract: Published literature strongly supports the use of water-soluble contrast as a predictive test for non-operative resolution of adhesive small bowel obstruction. Although Gastrografin does not cause resolution of small bowel obstruction there is strong evidence that it reduces hospital stay in those not requiring surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(42 citation statements)
references
References 21 publications
1
41
0
Order By: Relevance
“…The follow-through examination can in some cases take up to 24-48 h to perform before one can tell whether the obstruction is complete and needs surgical attention. Most studies consider that the water-soluble contrast medium Gastrografin Ò predicts the likelihood of operation, but does not reduce the need for surgical intervention [8,13,15], which in contrast has been reported by some authors [11]. Biondo et al [8] have shown that a follow-through examination with GastrografinÒ in patients suffering from adhesive small bowel obstruction shortens the hospital stay compared to the patients treated conservatively without GastrografinÒ.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The follow-through examination can in some cases take up to 24-48 h to perform before one can tell whether the obstruction is complete and needs surgical attention. Most studies consider that the water-soluble contrast medium Gastrografin Ò predicts the likelihood of operation, but does not reduce the need for surgical intervention [8,13,15], which in contrast has been reported by some authors [11]. Biondo et al [8] have shown that a follow-through examination with GastrografinÒ in patients suffering from adhesive small bowel obstruction shortens the hospital stay compared to the patients treated conservatively without GastrografinÒ.…”
Section: Discussionmentioning
confidence: 96%
“…According to most current patient management protocols, the diagnosis of complete obstruction will reveal itself only after a radiological examination, plain abdominal film and subsequent follow-through with Gastrografin Ò , alone or in combination with Barium [13]. The follow-through examination can in some cases take up to 24-48 h to perform before one can tell whether the obstruction is complete and needs surgical attention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If contrast fluid is visible in the cecum within 24 h after instillation this points to partial adhesive small bowel obstruction and predicts resolution. 55 Treatment Patients with small bowel obstruction require careful evaluation and management. Although it is a common problem in postoperative patients there are no strict rules or protocols for the management of patients with bowel obstruction.…”
Section: Diagnosismentioning
confidence: 99%
“…The use of oral Gastrografin® (Schering, Berlin, Germany), a water-soluble contrast medium, has previously been evaluated to predict the need for surgery, 6,7 to estimate whether it could shorten the resolution of a SBO and the hospital stay related to SBO, 8,9 and to investigate its potential therapeutic value. 8,10 -12 These studies have proved that Gastrografin® has a place in SBO diagnosis, 13 although its therapeutic role is not well-established. 14 The aim of this prospective study was to evaluate, in patients initially treated nonoperatively, the usefulness and the impact of a protocol using CT-scans and oral Gastrografin® in the management of adhesive SBO.…”
mentioning
confidence: 99%